Study of the Morphological, Electrical and Optical Properties of Ca4SrCu3Ti4O12 Ceramic (Chemical Engineering Research Bulletin, 2026)
The objective of this study was to investigate the microstructure, electrical resistivity and optical properties of Calcium strontium copper titanate (Ca4SrCu3Ti4O12) ceramic. To achieve this, a two-step milling process was employed in the solid-state method for the preparation of Ca4SrCu3Ti4O12 ceramics. The ceramic’s morphology was analyzed using Field Emission Scanning Electron Microscopy (FESEM), and the findings indicate a non-uniform microstructure consisting of two distinct grain types: smaller grains and larger grains. The optical properties of the prepared ceramics was determined by UV visible spectroscopy and found that absorption of light decreases at longer wavelength meanwhile the transmittance increases sharply with increasing the light wavelength. The band gap value of CSCTO is 5.91 eV. Resistivity of the ceramic was calculated by utilizing precision impedance analyzer.Chemical Engineering Research Bulletin : 24 (Issue 1) :41-46